The Miroir des dames in Fifteenth-Century England. (2nd December 2021) - Mattison, J R
Abstract: This article outlines the circulation and readership of a continental French text called the Miroir des dames in England during the fifteenth century. Three surviving manuscripts can be connected with England: one belonged to the Duke of Bedford, another to Henry VII, and a third was created in England and copied from Bedford's manuscript. Documentary evidence indicates that at least two further manuscripts of the Miroir circulated in England. These manuscripts and references demonstrate the continued reading and copying of French texts in England among a select circle of bibliophiles.